Improving IPS Learning Outcomes for Elementary School Students in Each Class Using the Problem Based Learning Model - Didi Syahrir; Yeni Erita; Feby KURNIAWAN; Vany Qhairum Nisa UTAMI (RADINKA JAYA UTAMA PUBLISHER, 2023)
Learning in a classroom is fairly passive because it just involves listening, completing homework, and reading books. Because of the lack of connection between students and professors or between students, learning is unproductive. The poor student learning outcomes are a result of this. The goal of this study is to examine how the problem-based learning (PBL) approach is used to enhance primary students' social studies learning outcomes. applying the meta analysis method in research. The process of gathering data involved searching Google Scholar for electronic journals and reading library materials. 16 periodicals and 4 student theses served as the data sources for this study. In a qualitative description, data analysis was done. Based on the results of the analysis, it was found that the problem-based learning model was able to improve student learning outcomes from the lowest 8.9% to an average increase of 30%. This shows that the problem-based learning model is effective in improving the social studies learning outcomes of elementary school students. The implications of this research are expected to assist teachers in choosing the right learning model to improve student learning outcomes.